2018
DOI: 10.1007/s10439-018-2034-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heated CO2 Insufflation in Minimising Surgical Wound Contamination During Open Surgery

Abstract: The primary source of infections in open surgeries has been found to be bacteria and viruses carried into the surgical wound on the surfaces of skin particles shed by patients and surgical staff. In open cardiac surgeries, insufflation of the wound with carbon dioxide is used to limit the quantity of air able to enter into the heart, avoiding air embolisms when the heart is restarted. This surgical technique has been evaluated as a method of limiting the number of skin particles able to enter into the wound, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…As a result, the CFU number decreased from an average value of 7.75 (without de-airing) to 2.75. This finding is consistent with the results of Persson and van der Linden [ 16 ] and Baumann and Cater [ 18 ], who showed that de-airing with carbon dioxide might prevent direct airborne contamination during cardiac surgery. Further experiments in our study demonstrated that using carvacrol-loaded membranes instead of neat polyamide membranes made it possible to decrease the contamination level by another 27% (decrease in the average CFU level from 2.75 to 2).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…As a result, the CFU number decreased from an average value of 7.75 (without de-airing) to 2.75. This finding is consistent with the results of Persson and van der Linden [ 16 ] and Baumann and Cater [ 18 ], who showed that de-airing with carbon dioxide might prevent direct airborne contamination during cardiac surgery. Further experiments in our study demonstrated that using carvacrol-loaded membranes instead of neat polyamide membranes made it possible to decrease the contamination level by another 27% (decrease in the average CFU level from 2.75 to 2).…”
Section: Resultssupporting
confidence: 92%
“…According to the literature, the most often applied flow rates in open surgical wound ventilation in Japan range from 2 to 5 L/min [ 15 ]. Other studies have indicated flow rates of interest as 2–10 L/min [ 14 ], 5 and 10 L/min [ 16 ], 5 L/min [ 17 ], and 10 L/min [ 18 ]. We selected a 5 L/min flow rate of carbon dioxide through the membrane for our experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations